AMPK alleviates oxidative stress‑induced premature senescence via inhibition of NF-κB/STAT3 axis-mediated positive feedback loop. (October 2020) - Han, Xiaojuan; Zhang, Tianying; Zhang, Xiaohua; Zhang, Ruisan; Lao, Kejing; Mi, Yajing; Gou, Xingchun
Highlights: SIPS is accompanied by a dynamic fluctuation of NF-κB and STAT3 activation, and SASP production. STAT3 signalling mediates the SASP-induced paracrine senescence. AMPK prevents oxidative stress-induced senescence via inhibition NF-κB/STAT3 signalling -mediated positive feedback loop. Abstract: Stress-induced premature senescence (SIPS) is characterized by the secretion of a variety of inflammatory cytokines, chemokines, and proteases, which are defined collectively as the senescence-associated secretory phenotype (SASP). AMP-activated protein kinase (AMPK) activation contributes to SIPS prevention, and the impact of AMPK on SASP may be included, but the mechanisms governing this phenomenon have not elucidated. In this study, we showed that SIPS is accompanied by a dynamic fluctuation of NF-κB activation, which induces SASP production, whilst reinforcing and amplifying local STAT3 signalling and subsequently enhancing downstream senescence. NF-κB and STAT3 inhibitors attenuate oxidative stress-induced senescence in a time-dependent manner. Conditioned medium (CM) from senescent cells rich in SASP factors can induce growth arrest and promote senescence in healthy cells; accordingly, a STAT3 inhibitor blunts the SASP-induced senescence, indicating a positive feedback mechanism via the NF-κB/STAT3 pathway that sustains SASP production and promotes senescence. In addition, we confirmed that AMPK negatively regulates SASP production and senescence development associated with NF-κB/STAT3 inhibition. In summary, our results suggest that AMPK prevents oxidative stress-induced senescence development via inhibiting the NF-κB/SASP/STAT3 signalling mediated positive feedback loop.